Beyond Legal Status: Multidimensional Well-Being in Formal and Dispensated Marriages in Lombok - Muniroh; Masnun Tahir; Mohammad Abdun Nasir; Ahyar; Zaidi; Hafizin (Lembaga Bale Literasi, 2026)
This study examines the multidimensional well-being of married couples based on marital pathways (formal marriage vs. marriage dispensation) in Lombok, Indonesia. While early marriage is often associated with negative outcomes, this research aims to provide a more nuanced understanding of its implications for psychological, social, and spiritual well-being. Using a mixed-methods convergent parallel design, quantitative data were collected from 697 couples and analyzed using MANOVA and hierarchical regression, complemented by qualitative data from 24 in-depth interviews analyzed thematically. The results show no significant difference in psychological well-being (p = 0.068), indicating adaptive equivalence between groups. However, couples in marriage dispensation report significantly higher social (?²p = 0.019) and spiritual well-being (p = 0.016; ?²p = 0.008), despite small effect sizes. Sociodemographic factors do not significantly moderate these relationships (Adjusted R² = 4.8%–7.8%). These findings suggest that well-being is shaped more by social processes such as communal integration, crisis negotiation, and meaning-making than by legal status or structural factors. The study contributes by proposing a processual framework of marital well-being. However, higher well-being among dispensation couples does not justify early marriage, but reflects adaptive responses within specific socio-cultural constraints